2017
DOI: 10.1007/s11046-017-0141-9
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Combined Antifungal Agents Against Multidrug-Resistant Candida glabrata Strains

Abstract: In this study, we evaluated the in vitro activity of echinocandins, azoles, and amphotericin B alone and in combination against echinocandin/azole-sensitive and echinocandin/azole-resistant Candida glabrata isolates. Susceptibility tests were performed using the broth microdilution method in accordance with the Clinical and Laboratory Standards Institute document M27-A3. The checkerboard method was used to evaluate the fractional inhibitory concentration index of the interactions. Cross-resistance was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In recent years, many approaches for the combination therapy have been proposed to treat infectious diseases. [11][12][13][14][15] This is very important, particularly, to counter the phenomenon of the multi-drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many approaches for the combination therapy have been proposed to treat infectious diseases. [11][12][13][14][15] This is very important, particularly, to counter the phenomenon of the multi-drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…10 The use of antibiotic combinations seems to be an important strategy to counter the phenomenon of drug resistance. [11][12][13] Chloroquine (CQ) and fluconazole (FLZ) exhibited a synergistic effect against FLZ-resistant isolates of C. albicans. 14 We earlier showed that liposomal-CQ increased the efficacy of FLZ against less susceptible isolate of Cryptococcus neoformans.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated afore, susceptibility testing of molds to echinocandins may be problematic due to inability to establish clear-cut MIC values, but is evaluated by the MEC. A recent study in Brazil ( Denardi et al, 2017 ) explored by the broth micro-dilution method of EUCAST and using the EUCAST-proposed breakpoints the in vitro susceptibility of 105 clinical and environmental strains of A. fumigatus and A. flavus to the antifungal drugs: amphotericin B, azoles, and echinocandins. They found that there were differences among the echinocandins (caspofungin, micafungin, and anidulafungin) as to activity and also variability as to susceptibility of the Aspergillus spp.…”
Section: Human Aspergillosis: In Vitro Assessment mentioning
confidence: 99%
“…As to in vitro susceptibility testing of antifungal combinations against Aspergillus spp.—here too are a number of reports in the literature. A recent article by Denardi et al (2017) reports on susceptibility testing of A. fumigatus to antifungal–drug combinations. The authors evaluated combinations of triazoles and echinocandins on itraconazole-resistant strains, using two methods: the checkerboard assay and the E -test.…”
Section: Human Aspergillosis: In Vitro Assessment mentioning
confidence: 99%
“…Another study found a similar degree of synergism with anidulafungin against various species of Candida [ 31 ]. Conversely, other studies with C. glabrata demonstrated a lack of synergy with the combinations of amphotericin B and echinocandins [ 32 ]. Although most interactions were deemed indifferent by the checkerboard method in the study of Serena et al on the combination of amphotericin B with micafungin, there was synergism against some strains that were further analysed by time–kill methodology and the combination demonstrated a fast-killing activity against them [ 33 ].…”
Section: Discussionmentioning
confidence: 95%